Moringa Leaves-Added Food, Baby Massage, and Tui Na Massage to Reduce Stunting Rate on Young Children in Indonesia - Eka Sutrisna; Husna Maulida; Fauzan Saputra; Yunitasari; Arista Ardila; Suriani; Ristiani (Jurnal Kesehatan Masyarakat, 2025)
Stunting remains a significant public health issue in Indonesia, particularly in Aceh Province, where the prevalence reached 33.18% in 2021 exceeding the WHO threshold. In North Aceh District, 14.3% of children under five were stunted, with Simpang Keramat District reporting one of the highest rates (35%). This study aimed to evaluate the effectiveness of a combined intervention Moringa leaf-supplemented food within a balanced diet, baby massage, and Tui Na massage in improving the nutritional status of stunted children aged 0–2 years. A quasi-experimental pre-post design was used, involving 50 stunted children divided equally into treatment and control groups. The intervention was conducted over 2.5 months. Paired t-test results showed significant increases in weight (t24 = -6.656, p < .000) and height (t24 = -3.244, p < .003) in the treatment group compared to the control group. These findings suggest that combining dietary fortification using locally available Moringa leaves with physical stimulation through massage therapy can effectively enhance growth outcomes. Given the multifactorial nature of stunting, this study recommends that nurses and health practitioners incorporate both nutrition-based interventions and sensory-stimulating therapies to address growth delays in young children, particularly in high-risk areas such as Aceh.